Ecuador from boom to crisis: fiscal policy to postpone adjustment - Acosta González, Nicolás (2018)
Debt issuance was an important source of income for Ecuador since 2016. The country was already facing a complicated fiscal scenario since 2013. When the oil price collapsed and an earthquake of 7,8 magnitude hit the coast, fiscal balance got highly deteriorated. In this paper, through correlational treatment of the variables we issue explanations and hypothesis about fiscal sustainability, quality of spending, and some unconventional instruments. We conclude that, despite the use of these instruments to postpone a fiscal adjustment, the situation is already unsustainable. DOI: https://doi.org/10.31164/bcoyu.17.2018.665 URL: http://revistas.uta.edu.ec/erevista/index.php/bcoyu/article/view/665